Biphasic clinical course among Kenyan children with cerebral malaria - Gwer, S; Punt, J; Idro, R; Mwamuye, I; Gatakaa, H; Charles, R; Marsh, K (2008)
Background: Cerebral malaria is the most severe neurological complication of Falciparum malaria. It is associated with a significant risk of death and neurological sequelae. A biphasic clinical picture is associated with an even greater risk of neurological sequelae. Objective: To examine the incidence and clinical characteristics of a biphasic clinical course in children with cerebral malaria and to study its relationship with outcome Method: We undertook a retrospective study of children admitted to Kilifi District Hospital with a history of impaired consciousness and Falciparum infection between January 1994 and December 2004. We identified children with a biphasic clinical course and examined their clinical characteristics and outcome against that of those with a single clinical course. Results: Out of 587 children with cerebral malaria, 11 were found to have a biphasic clinical course often heralded by recurrence of seizures. This clinical pattern was associated with a greater incidence of neurological sequelae but no death. Conclusion: We speculate that a biphasic clinical course may occur due to recurrent seizures, co-morbidity and reperfusion of cerebral areas previously clogged by parasitized red blood cells. A prospective examination of this group may shed more light on causality and enlighten further on pathogenesis of cerebral malaria. © 2002 African Journal of Neurological Sciences. All rights reserved.